The Effect of Empowering Leadership on Work Engagement: The Mediating Role of Psychological Empowerment and the Moderating Role of Power Distance Orientation among Generation Z Employees in Surabaya - Meilia Putri Alamanda; Ronny Ronny; Shinta Setia (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
Work engagement has become a critical concern in contemporary organizations, particularly as workforce dynamics continue to evolve. Among emerging employee groups, Generation Z demonstrates distinct expectations regarding leadership, autonomy, and workplace values, making it essential to understand the factors that foster their engagement at work. This study examines how empowering leadership shapes work engagement by incorporating psychological empowerment as an underlying mechanism and power distance orientation as a contextual boundary condition. Using a quantitative approach, data were collected through a survey and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that empowering leadership positively and significantly enhances work engagement. Psychological empowerment partially mediates this relationship, indicating that empowering leadership strengthens employees’ sense of meaning, competence, self-determination, and impact, which in turn fosters greater engagement. Furthermore, power distance orientation moderates the relationship between empowering leadership and psychological empowerment, with stronger effects observed among individuals with lower power distance orientation. These findings highlight the importance of empowering leadership in fostering employee engagement by addressing both psychological mechanisms and individual cultural orientations.